Notes on four pholcid spiders (Araneae: Pholcidae) described by T. Thorell from Southeast Asia - Yao, Zhiyuan; Tavano, Maria; Li, Shuqiang (Zootaxa, 2013)
The Southeast Asian pholcids Belisana tauricornis Thorell, 1898, Pholcus gracillimus Thorell, 1890, P. quinquenotatus Thorell, 1878 and Spermophora thorelli Roewer, 1942 are redescribed on the basis of the type material.